Implementation of Feminism in an Islamic Perspective - Isman, Nofa; H, Lola Hervina (Jurnal Kawakib, 2023)
Feminism is a movement that results from the awareness that women are discriminated against and always under men. This study aims to describe the notion of feminism, to describe the history of feminism, and to describe the implementation of feminism from an Islamic perspective. The method used is a qualitative approach, library research, and descriptive methods. The results of the research are the notion of feminism, which linguistically means feminine, and in terms, it is a movement or reaction to the liberation of women in demanding discriminated rights which become a concept, ideology, and belief or belief understanding of equal rights between women and men. From its history, the term feminism first appeared in France in 1908 AD by Charles Fourier, and its development was divided into three waves. From its implementation, there are many negative impacts of feminism which refers to promiscuity which is contrary to Islam.